(untitled) (IASH Indian Journal of Arid Horticulture, 2024)
Among 29 physiological traits in bottle gourd varieties, highly significant correlation in FL and FW with FG and NFMF, respectively (r=+1.00; P≤0.05) were observed. Likewise, FW with FL (r=+1.00; P≤0.001). High magnitude and significant correlation were found between IL and LPL (r=+1.00; P≤0.01). Similarly, high magnitude and significant correlation links were noticed in NFFF (r=+1.00; P≤0.01), DFFA (r=+1.00; P≤0.05) and NMFP (r=+1.00; P≤0.01) with LW; DFFA with NFFF(r=+1.00; P≤0.05); NMFP with NFFF (r=+1.00; P≤0.05); NFP with NFFP with NFFF (r=+1.00; P≤0.01); SYH with SYP with NFFF (r=+1.00; P≤0.001); FYP with SYP (r=+0.99; P≤0.01), SYH (r=+0.99; P≤0.01) and PL (r=+1.00; P≤0.01); FYH with SYP (r=+0.99; P≤0.01), SYH (r=+0.99; P≤0.01), PL (r=+1.00; P≤0.01) and FYP (r=+1.00; P≤0.001); RT with NSF (r=+1.00; P≤0.05); AAS with NSF (r=+1.00; P≤0.05) and RT (r=+1.00; P≤0.001); SYF with NSF (r=+1.00; P≤0.05). The findings indicate that Thar Avani demonstrates strong performance under semi-arid conditions, showcasing substantial variability that can be leveraged in breeding programs focused on yield improvement.